2016
DOI: 10.1139/cjm-2015-0350
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and viral determinants of retroviral nuclear entry

Abstract: Retroviruses must integrate their cDNA into the host genome to generate proviruses. Viral DNA-protein complexes interact with cellular proteins and produce pre-integration complexes, which carry the viral genome and cross the nuclear pore channel to enter the nucleus and integrate viral DNA into host chromosomal DNA. If the reverse transcripts fail to integrate, linear or circular DNA species such as 1-and 2-long terminal repeats are generated. Such complexes encounter numerous cellular proteins in the cytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 150 publications
0
25
1
Order By: Relevance
“…Plant-based culture media provide the culturable microbiome with diverse nutrients at concentrations that mimic the root milieu. Additionally, plant materials in the form of plant-based culture media ( 51 , 62 ) or as a supplement to enrich standard artificial culture media ( 44 ) impaired the swarming motility of bacteria on agar plates, thereby halting their expansive progression and restricting the dominance of larger slimy colonies. In many cases, these slimy colonies masked the presence of some small colonies and/or μ-colonies.…”
Section: Discussionmentioning
confidence: 99%
“…Plant-based culture media provide the culturable microbiome with diverse nutrients at concentrations that mimic the root milieu. Additionally, plant materials in the form of plant-based culture media ( 51 , 62 ) or as a supplement to enrich standard artificial culture media ( 44 ) impaired the swarming motility of bacteria on agar plates, thereby halting their expansive progression and restricting the dominance of larger slimy colonies. In many cases, these slimy colonies masked the presence of some small colonies and/or μ-colonies.…”
Section: Discussionmentioning
confidence: 99%
“…found that bacterial diversity (H’) significantly correlated with soil moisture in the Tibetan permafrost region. In a high Arctic polar oasis, Banerjee et al 42. found soil moisture was the key edaphic factor which drove the archaeal community structure.…”
Section: Discussionmentioning
confidence: 99%
“…Both the p12 N-and C-terminal domains are required to be in cis (5), suggesting that p12 acts as a bridge between the CA within the PIC and the host chromatin. As MLV requires cells to proceed through mitosis for integration (12) and lacks the interactions with host proteins involved in active nuclear transport of HIV (13,14), p12 is proposed to function in retaining the PIC in the nucleus postmitosis (5,8,9). Alternate chromatin tethers functionally replacing the C-terminal function did not alter the MLV integration profile, ruling out the possibility that the p12 chromatin tether is the driving determinant for integration site selection (8).…”
mentioning
confidence: 99%